Cardiac involvement in consecutive elite athletes recovered from Covid-19: A magnetic resonance study - Malek, L. A.; Marczak, M.; Milosz-Wieczorek, B.; Konopka, M.; Braksator, W.; Drygas, W.; Krzywanski, J. (Journal of Magnetic Resonance Imaging, 2021)
Magnetic resonance (MR) studies suggested cardiac involvement post-Covid-19 in a significant subset of affected individuals, including athletes. This brings serious clinical concerns regarding the potential need for in-depth cardiac screening in athletes after Covid-19 before return to play. The aim of this study was to gain further insight into the relation between Covid-19 and cardiac involvement in professional athletes. This was a retrospective cohort study, in which 26 consecutive elite athletes (national team, Olympians, top national league players; median age 24 years, interquartile range [IQR] 21-27, 81% female) were included. At 1.5 T including balanced steady-state free precession cine imaging, T1 and T2-mapping using Myomaps software (Siemens), dark-blood T2-weighted images with fat suppression, and late gadolinium enhancement (LGE) with phase-sensitive inversion recovery sequence were used. The athletes had mainly asymptomatic or mild course of the disease (77%). They were scanned after a median of 32 days (IQR 22-62 days) from the diagnosis. MR data were reviewed by three independent observers, each with >10 years cardiac MR experience. Native T1, T2, extracellular volume, and T2 signal intensity ratio were calculated. Diagnosis of acute myocarditis was based on modified Lake Louise criteria. Statistical analyses used were Pearson correlation and Bland-Altman repeatability analysis. At the time of MR the athletes had no pathologic electrocardiogram abnormalities or elevated troponin levels. MR did not reveal any case of acute myocarditis. Cardiac abnormalities were found in five (19%) athletes, including four athletes presenting borderline signs of isolated myocardial edema and one athlete showing nonischemic LGE with pleural and pericardial effusion. Another athlete had signs of persistent lung congestion without cardiac involvement. We have shown that in a small group of elite athletes with mainly asymptomatic to mild Covid-19, lack of electrocardiographic changes, and normal troponin concentration 1-2 months after the diagnosis, there were no signs of acute myocarditis, but 19% of athletes had some abnormalities as assessed by cardiac MR.